2014
DOI: 10.1073/pnas.1321355110
|View full text |Cite
|
Sign up to set email alerts
|

Increasing socioeconomic disparities in adolescent obesity

Abstract: Significance Childhood and youth obesity represent significant US public health challenges. Recent findings that the childhood obesity ‘‘epidemic’’ may have slightly abated have been met with relief from health professionals and popular media. However, we document that the overall trend in youth obesity rates masks a significant and growing class gap between youth from upper and lower socioeconomic status (SES) backgrounds. Until 2002, obesity rates increased at similar rates for all adolescents, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(192 citation statements)
references
References 29 publications
7
173
1
8
Order By: Relevance
“…Asupan energi yang besar pada anak-anak yang mengonsumsi fast food dan soft drink dalam jumlah yang banyak tanpa diimbangi dengan aktivitas fisik yang cukup dapat menyebabkan terjadinya kegemukan [12]. Masa anakanak adalah masa pertumbuhan dan perkembangan sehingga kegemukan pada masa anak menyebabkan semakin banyaknya jumlah sel otot dan tulang rangka, sedangkan kegemukan pada orang dewasa hanya terjadi pembesaran sel-sel saja sehingga kemungkinan penurunan berat badan ke normal akan lebih mudah [13]. Anak yang mengalami kegemukan akan berisiko tinggi menderita kegemukan pada masa dewasa dan berpotensi mengalami berbagai penyebab kesakitan dan kemati-an antara lain penyakit kardiovaskular dan diabetes melitus serta akibat yang ditimbulkan kegemukan ini akan mem-punyai dampak terhadap tumbuh kembang anak itu sendiri [14].…”
Section: Pendahuluanunclassified
“…Asupan energi yang besar pada anak-anak yang mengonsumsi fast food dan soft drink dalam jumlah yang banyak tanpa diimbangi dengan aktivitas fisik yang cukup dapat menyebabkan terjadinya kegemukan [12]. Masa anakanak adalah masa pertumbuhan dan perkembangan sehingga kegemukan pada masa anak menyebabkan semakin banyaknya jumlah sel otot dan tulang rangka, sedangkan kegemukan pada orang dewasa hanya terjadi pembesaran sel-sel saja sehingga kemungkinan penurunan berat badan ke normal akan lebih mudah [13]. Anak yang mengalami kegemukan akan berisiko tinggi menderita kegemukan pada masa dewasa dan berpotensi mengalami berbagai penyebab kesakitan dan kemati-an antara lain penyakit kardiovaskular dan diabetes melitus serta akibat yang ditimbulkan kegemukan ini akan mem-punyai dampak terhadap tumbuh kembang anak itu sendiri [14].…”
Section: Pendahuluanunclassified
“…Cases of obesity and its associated disorders are increasing at accelerating and alarming rate worldwide (Frederick et al, 2014). Obesity is associated with immune function impairment, affecting both innate and adaptive immune systems (Andersen et al, 2016, Exley et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…While high income people can afford healthy food products, adolescents with low SES do not always eat properly because of poverty 57 . It has also been reported that female adolescents from larger families and males from families with higher incomes were less likely to be overweight and consumed less calories than their low SES peers 58 .…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 98%